Export Stimuli Perceived By the Managers of Industrial Companies: The Case of the Tunisian SME - Hammami, Ilhem; Zghal, Mustapha (British Journal of Marketing Studies, 2016)
The perception of export stimuli is particularly important and was identified by several studies as essential factor of the export success of the SME. An exploratory survey with Tunisian exporters SME allowed to identify which stimuli exports are perceived by the managers.